The cultural other and the nearest neighbor: Han–Nuosu relations in Zhaojue County, Southwest China. Issue 2 (2nd April 2016) - Hein, Anke; Zhao, Deyun
Abstract : Greater Liangshan is one of the few regions of China where, among 70–80% of Nuosu, the Han are a minority. Instead of the much more common phenomenon of 'Hanification, ' here we can observe Han absorbing traits of other ethnic groups. Based on two seasons of fieldwork combined with historical texts and previous ethnographic research, this paper discusses this phenomenon, raising issues of ethnic identity and the influence of local circumstances on interethnic relations. Throughout the paper, it becomes clear that there is no simple dichotomy between Han and Nuosu, but that the situation is considerably more complex. The Nuosu fall into several castes, and the Han settlers had two different experiences. Some were captured as slaves and tried to become fully Nuosu. Ethnic relations in the Greater Liangshan are thus highly complex and require more research to be thoroughly understood.